Analysis of Social Media Literacy in Adolescents in Educational Theme Video Content - Muhammad Abrar Parinduri; Larasati Nur Karomah (Ta'dib, 2023)
This quantitative study aims to determine and describe social media literacy in adolescents in Langkat regency. The study sample consisted of 88 teenagers. Data collection techniques were collected using online questionnaires prepared using individual competence indicators such as media use, critical thinking, and communication. The results showed that there still needs to be more social media literacy in the essential aspect of thought, namely repeated examination of information circulating on social media by adolescents. The recommendation of the results of this study is the importance of providing education by related parties such as the school environment and families so that it can help adolescent social media literacy